2015
DOI: 10.1177/1356766715604663
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the role of brand identification and brand love in generating higher levels of brand loyalty

Abstract: The aim of this study is to develop a model that integrates brand identity, brand-life congruence, customer hotel brand identification (CHBI), and brand love into one model and to test its predictive power in explaining brand loyalty. The survey data were gathered from (432) guests who were staying in seven well-known hotels located in Jordan. Data were analyzed using a structural equation modeling SmartPLS2.0. Four key findings emerged from the current research. First, compared to brand identity, brand-lifest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
88
1
10

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(108 citation statements)
references
References 123 publications
9
88
1
10
Order By: Relevance
“…Brand love, which comes from three basic elements such as enthusiasm, intimacy, and commitment, plays an undeniable role in the presence of a loyal customer in the long run. This finding is also consistent with the results of Alnawas and Altarifi (2016) (19). Love creates motivation in people that causes them to give maximum efforts towards brand success.…”
Section: Discussionsupporting
confidence: 92%
“…Brand love, which comes from three basic elements such as enthusiasm, intimacy, and commitment, plays an undeniable role in the presence of a loyal customer in the long run. This finding is also consistent with the results of Alnawas and Altarifi (2016) (19). Love creates motivation in people that causes them to give maximum efforts towards brand success.…”
Section: Discussionsupporting
confidence: 92%
“…Researchers have demonstrated the positive and significant relationship between brand love and brand loyalty (e.g., Alnawas and Alrarifi 2015;Bairrada et al 2018;Batra et al 2012;Bıçakcıoglu et al 2018;Carroll and Ahuvia 2006;Drennan et al 2015;Huang 2017;Kim et al 2008;Thomson et al 2005;Wallace et al 2014). Likewise, the importance of brand love in brand loyal behaviors was reported in several studies of fashion brands.…”
Section: Effect Of Brand Love On Brand Loyal Behaviorsmentioning
confidence: 97%
“…Thus, developing brand love is considered as a primary goal for customer relationship marketing (CRM) and brand management (Pawle and Cooper 2006). Accordingly, there has been a substantial amount of academic research on brand love and its relationship to consumer behaviors such as shopping/brand experiences (Pandowo 2016;Sarkar et al 2019), purchase intentions (Fetscherin 2014;Pawle and Cooper 2006), brand loyalty (Alnawas and Alrarifi 2015;Drennan et al 2015;Fournier 1998;Huang 2017;Thomson et al 2005;Wallace et al 2014), brand trust (Albert and Merunka 2013;Langner et al 2015), positive word-of-mouth (Karjaluoto et al 2016;Wallace et al 2014), and willingness to pay (Albert and Merunka 2013;Thomson et al 2005). Fournier (1998) argued that consumers are capable of emotionally bonding with certain brands in a similar manner to developing interpersonal relationships and her claim was supported by later research that found consumers can build emotional connections with brands just like developing love in a relationship (Carroll and Ahuvia 2006;Wallace et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…To a lesser extent, confusion exists in relation to the outcomes of brand love, with trust being cited as a dimension of brand love (Albert et al, 2008), an antecedent of brand love (Albert and Merunka, 2013) and an outcome of brand love (Loureiro et al, 2012). Nevertheless, there appears to be some consensus over other brand love outcomes with purchase intention (Fetscherin et al, 2014;Sarkar et al, 2012), word-of-mouth recommendation/advocacy (Fetscherin et al, 2014;Sarkar et al, 2012), loyalty (Carroll and Ahuvia, 2006;Loureiro et al, 2012;Roy et al, 2013;Alnawas and Altarifi, 2016) and commitment (Albert and Merunka, 2013;Loureiro et al, 2012;Garg et al, 2016) being cited as prominent outcomes. However, given the disparate operationalization of these outcome constructs across studies, it is suggested that consensus may be an apparition based on construct labelling, rather than construct measurement/validity.…”
Section: Brand Lovementioning
confidence: 99%